2021
DOI: 10.1007/s11172-021-3118-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of (5-oxo-6,7-dihydro-4H-[1,2,4]triazolo-[1,5-a]pyrimidin-6-yl)acetanilides based on the recyclization of N-arylitaconimides with 3-amino[1,2,4]triazoles

Abstract: A convenient method for the synthesis of 2-(2-R-5-oxo-6,7-dihydro-4H-[1,2,4]triazolo-[1,5-a] pyrimidin-6-yl)acetanilides based on the regioselective domino reaction of N-arylitaconimides with substituted 3-aminotriazoles was proposed. Presumably, the reaction pathway includes the conjugated aza-addition of the endo-nucleophilic center of triazole to imide, followed by the recyclization of the intermediate to triazolo [1,5-a]pyrimidine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Previous studies indicated that preferred conditions for the recyclization of itaconimides with heterocyclic binucleophiles involve boiling the reagents in isopropyl alcohol in the presence of acetic acid. 19 We found that the interaction of N-substituted 5-aminopyrazoles with itaconimides, when boiling the reagents in a mixture of different solvents with acetic acid in a 20:1 ratio, selectively produces the previously described pyrazolo[3,4- b ]pyridines 3a – l . Meanwhile, the recyclization of itaconimides with 4-substituted-2,5-aminopyrazoles under the same conditions yields new derivatives of pyrazolo[1,5- a ]pyrimidine 4a – k (Scheme 1 ).…”
Section: Table 1 Content Of Pyrazolo[15- ...mentioning
confidence: 87%
See 4 more Smart Citations
“…Previous studies indicated that preferred conditions for the recyclization of itaconimides with heterocyclic binucleophiles involve boiling the reagents in isopropyl alcohol in the presence of acetic acid. 19 We found that the interaction of N-substituted 5-aminopyrazoles with itaconimides, when boiling the reagents in a mixture of different solvents with acetic acid in a 20:1 ratio, selectively produces the previously described pyrazolo[3,4- b ]pyridines 3a – l . Meanwhile, the recyclization of itaconimides with 4-substituted-2,5-aminopyrazoles under the same conditions yields new derivatives of pyrazolo[1,5- a ]pyrimidine 4a – k (Scheme 1 ).…”
Section: Table 1 Content Of Pyrazolo[15- ...mentioning
confidence: 87%
“…Previous studies indicated that preferred conditions for the recyclization of itaconimides with heterocyclic binucleophiles involve boiling the reagents in isopropyl alcohol in the presence of acetic acid. 19 We found that the interaction of N-substituted 5-aminopyrazoles with itaconimides, when boiling the reagents in a mixture of different solvents with acetic acid in a 20:1 ratio, selectively produces the previously described pyrazolo [3,4-b]pyridines 3a-l. Mean-while, the recyclization of itaconimides with 4-substituted-2,5-aminopyrazoles under the same conditions yields new derivatives of pyrazolo [1,5-a]pyrimidine 4a-k (Scheme 1). However, unlike the analogous recyclization of maleimides, 16 in the case of unsubstituted aminopyrazole (R 1 , R 2 = H), no evidence of an alternative product 3a-l was observed under any conditions (boiling in mixtures with varying ratios of acetic acid to isopropyl alcohol, methanol, xylene, dimethylformamide, or in pure acetic acid).…”
Section: Paper Synthesismentioning
confidence: 88%
See 3 more Smart Citations